Caribbean Teachers' Perspectives on One-to-One ICT Programme for Enchancing Teaching and Learning: A Case Study of a Boys' High School - Onuoha, C.A.; Onuoha, P.C.; Ferdinand, D. (My University, 2016)
The purpose of this study was to document the perspectives of teachers who form an important stakeholder to the newly established eConnect and Learn (eCAL) programme in a Caribbean Island state.
Keywords: Educational technology